ANALISIS STILISTIKA DALAM ANTOLOGI PUISI CARA-CARA TIDAK KREATIF UNTUK MENCINTAI KARYA THEORESIA RUMTE & WESLLY JOHANNES - Septiana Lestari Harahap; IGA Mas Triadnyani; Ida Bagus Jelantik (Cahaya Ilmu Bangsa Institute, 2024)
This research uses the poetry anthology Cara-Cara Tidak Kreatif Untuk Mencintai as an object which is studied from a stylistic perspective. The poetry anthology Cara-Cara Tidak Kreatif Untuk Mencintai was chosen as the research object because it contains a lot of diction for expressing love. The analysis in this research includes analysis of the physical structure of poetry, the inner structure of poetry, and stylistic analysis related to the diction of love statements contained in the poetry anthology Cara-Cara Tidak Kreatif Untuk Mencintai. The theories used are Aminuddin's stylistic theory and Herman Waluyo's structural theory of poetry. The method used in collecting data is using the library study method with reading, listening and note-taking techniques. The method used is descriptive analytic. Based on the analysis, the following results were obtained. First, the poems that have been analyzed consist of diction, figurative meaning, symbols, images, figures of speech, themes, feelings, tone and atmosphere, and different messages. Second, the stylistics of expressing love used by poets in their poems does not mean to fatally violate norms in the use of communication language. The poet's style of language in conveying his thoughts and ideas is a personal characteristic that the poet is a free spirit.